Profiles of motivation and engagement in foreign language learning: Associations with emotional factors, academic achievement, and demographic features. (August 2022) - Li, Jiajing; King, Ronnel B.; Wang, Chuang
Abstract: Motivation and engagement have long been recognized as determinants of foreign language learning. However, prior studies have mainly used variable-centered approaches to explore their relationships with key learning-related outcomes. Individual differences in foreign language learners' motivation and engagement and how they are associated with other language learning factors remain underexplored. Therefore, we employed a person-centered approach (i.e., latent profile analysis) to identify profiles of motivation and engagement in foreign language learning among 532 Chinese university students. We conducted analyses of variance to explore the differences in emotional factors and academic performance across profiles. Finally, multinomial logistic regression analysis was utilized to investigate how demographic features differed across profiles. Four profiles were identified that characterized Chinese university students' motivation and engagement in foreign language learning. They were labeled as "Demotivated and Disengaged", "Motivated and Engaged", "Demotivated but Engaged", and "Moderately Motivated and Engaged". Results also indicated that these four profiles showed significantly different degrees of enjoyment, anxiety, and academic performance. "Motivated and Engaged" learners demonstrated the most adaptive outcomes, in contrast to "Demotivated and Disengaged" EFL learners. College major did not predict profile membership, but age, gender, and years of learning English did. Theoretical and practical implications are discussed. Highlights: Four profile groups were identified based on Chinese EFL learners' motivation and engagement. The four groups demonstrated significant differences in enjoyment, anxiety, and academic performance. Gender, age, and years of learning English predicted group membership.